2012
DOI: 10.1007/s10195-012-0205-z
|View full text |Cite
|
Sign up to set email alerts
|

Is computer-assisted total knee replacement for beginners or experts? Prospective study among three groups of patients treated by surgeons with different levels of experience

Abstract: BackgroundComputer-assisted total knee replacement (TKR) has been shown to improve radiographic alignment and therefore the clinical outcome. Outliers with greater than 3° of varus or valgus malalignment in TKR can suffer higher failure rates. The aim of this study was to determine the impact of experience with both computer navigation and knee replacement surgery on the frequency of errors in intraoperative bone cuts and implant alignment, as well as the actual learning curve.Materials and methodsThree homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
(21 reference statements)
0
25
0
1
Order By: Relevance
“…Immediate visual feedback that allows real time adjustments of cutting blocks means implants can be positioned with great accuracy and precision [1,27]. This in turn leads to less cutting errors and alignment outliers [1,22,25,27]. Our study has shown that these benefits can translate to good medium-term clinical function of TKA even in surgery performed by less experienced hands.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Immediate visual feedback that allows real time adjustments of cutting blocks means implants can be positioned with great accuracy and precision [1,27]. This in turn leads to less cutting errors and alignment outliers [1,22,25,27]. Our study has shown that these benefits can translate to good medium-term clinical function of TKA even in surgery performed by less experienced hands.…”
Section: Discussionmentioning
confidence: 64%
“…In other studies where similar comparisons have been performed, after 11-30 cases operative time differences have been seen to equalize. This is considered an acceptable learning curve for this procedure [1,22,26,27]. CAS allows trainees to achieve 5-year functional results with TKA that are comparable to a consultant surgeon experienced in the use of CAS at mid-term follow-up.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Secondly, the operating surgeon undertakes a high volume of TKAs annually, and it is possible that this level of experience positively influenced the results. The learning curve for beginner surgeons has been shown to be acceptably low with computer-assisted navigation systems, with the exception of a general increase in operative and tourniquet times during initial cases [21][22][23]. Additional research is required, however, to ascertain whether lessexperienced surgeons would encounter a similar learning curve with this particular PSI technology.…”
Section: Discussionmentioning
confidence: 99%
“…CAS) after a learning curve of 16 cases; this is called the breakeven point after which no statistically significant difference in surgical time is observed between the expert surgeon and the beginner using CAS. 20 In 2013, Nicholson et al raised an interesting issue regarding the "re-learning curve for conventional total knee arthroplasty following 30 consecutive computer assisted total knee arthroplasties". 21 A "re-learning curve" of 30 conventional TKAs was necessary to attain an average postoperative mechanical axis statistically indistinguishable from the average CAS mechanical axis (1.99 ).…”
Section: Accuracy and Precision In Surgical Techniquesmentioning
confidence: 98%